Evaluation of Customer Intention to Visit Destination of Halal EcoTourism using Structural Equation Modelling - Nashirah Abu Bakar , Sofian Rosbi , Kiyotaka Uzaki (International Journal of Advanced Science and Technology, 2020)
The objective of this study is to evaluate customer intention to visit destination of halal ecotourism using structural equation modelling. Destination of halal eco-tourism is place fortourism that educate visitors about environmental awareness and providing halal compliantentertainment. The methodology implemented in this study is using questionnaire method. Thedependent variable is customer intention to visit destination of halal eco-tourism. The fourindependent variables are brand equity, culture, quality and social. This framework using socialdistance theory. The number of respondents is 300 customers that have intention to visit tourismplaces. Then, the finding was analyzed using confirmatory factor analysis for pooled model.Then, the validity and reliability constructs of measurement model were validated using absolutefit, incremental fit and parsimonious fit. Next, structural model of path analysis using structuralequation modelling was performed. The result shows the absolute fit (RMSEA) is 0.029,incremental fit (CFI) is 0.997 and parsimonious fit (Chi-square/degree-of-freedom) is 1.247. Allof three model fit indexes indicate the measurement and structural model is good fit with data.Multiple regression analysis shows all four exogenous latent constructs indicates significantrelationship to endogenous latent construct namely customer intention to visit destination ofhalal eco-tourism. The novelty of this research is it provides a clear procedure for performingconfirmatory factor analysis for validating model fit with data. In the same time, four latentvariables have significant relationship to customer intention to visit destination of halal ecotourism